Strategi Penanaman Nilai Peradaban Islam dalam Merespon Globalisasi - Abdurrahim Yapono (TSAQAFAH, 2015)
This article aims to examine the meaning of Islamic civilization, its philosophy and foundation; the impact of globalization, opportunities and challenges to the Islamic civilization; and the value building strategy of the Islamic civilization in responding to the challenges of globalization. Islamic Civilization as a study of the socio-cultural and religious phenomenon, the methodological approach is not only through library data collection, but also through intuitive observation, because it involves the religious psychology and spiritual life of individuals and society. It aims to know the truth from four symptoms at once: perceived truth; logical empirical truth, empirical truth of ethics, transcendental truth. The next stage is verification of the data, comparison, analyzation and conclusions drawn qualitatively; presented by descriptive analytical in order to reach the answer to the phenomenon studied. In conclusion, Islamic civilization is a socio-religious phenomenon that exists not only in this age, but has existed since the time of Prophet Muhammad (SAW). By introducing Islamic civilization values that are universal, blessing for the universe, across time and space, has three pillars integrated primary, namely faith, obedience and ih}sân (morals/Sufism). So by its nature, the values of the Islamic civilization will continue to shine until the Day of Resurrection in line with the human need for religion. Islamic civilization values for building opportunity is wide open, as well as the challenges being very diverse. Being a strategy that can be applied to respond to global challenges with a solid organizational structure, strategy, systems, style, skills, share of value, and staff.